Con las Alas Abiertas para Volar. Un camino de Vida Artístico en Construcción desde el estudio de la creación escénica y audiovisual (2023)
In these pages, I want to reconstruct my artistic life story through a qualitative-focused narrative, where I seek to give testimony of my acquired experiences and knowledge through description and documentation. Helped by some previously designed interviews, I long to convey the experiences I have had alongside the people who have influenced and inspired my artistic path. These conversations, along with bibliographic references, will enrich the narration.